Integrative taxonomy sheds light on an old problem: the Ulota crispa complex (Orthotrichaceae, Musci). (April 2016) - Caparrós, Rut; Lara, Francisco; Draper, Isabel; Mazimpaka, Vicente; Garilleti, Ricardo
Abstract : The combined use of morphological and molecular analyses has been proven to be useful in resolving taxonomic complexes with hidden diversity. In bryology, however, integrative taxonomy has rarely been employed to revisit relevant old, unresolved problems. One of these classical controversies is whether the Ulota crispa complex comprises one or three species. To elucidate this, an exhaustive morphological revision, based on numerous herbarium and fresh specimens from most of the Holarctic areas in which U. crispa has been reported, and molecular analyses, using one nuclear (ITS2) and three plastid ( trnG, trnL‐trnF, atpB‐rbcL ) loci on a selection of representative specimens, have been performed. The results unambiguously point to the existence of three morphotypes, ascribable to the previously described Ulota crispa s.s ., U. crispula and U. intermedia, which can be differentiated by an ample set of qualitative and quantitative morphological characters. A phylogenetic reconstruction based on molecular data is proposed, including samples of these morphotypes in a framework of another ten Ulota spp. and two Orthotrichum and two Zygodon spp. According to the results, the samples belonging to these morphotypes are placed in three independent and coherent monophyletic clades, indicating that they represent three closely related, but independent, species. The origin and development of the taxonomic debate around U. crispa and related taxa are discussed to illuminate the reasons for this historical confusion. The analysis of the geographical origin of the studied samples shows that all three species are widely distributed throughout the Northern Hemisphere, although with different ranges. Ulota crispula has an amphi‐Atlantic range, whereas U. crispa and U. intermedia display broader disjunct ranges; only in Europe do the three species co‐occur. A key to the three species and updated detailed descriptions are provided.